PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPAS MATERI BENCANA ALAM PADA PESERTA DIDIK KELAS V SDN TENGGILIS MEJOYO 1 SURABAYA - Nufarinda Jazilatul Khikmiyah; Wahyu Susiloningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the Discovery Learning model on the learning outcomes of students in the IPAS subject at Year 5 of SDN Tenggilis Mejoyo 1, Surabaya. To this day, the learning activities remain predominantly teacher-centred and do not provide opportunities for students to develop independently through discovery and critical thinking activities. The research employs a qualitative approach. The population consists of classes V-A and V-B, each comprising 29 students, which serve as the sample for this study. The data collection technique used is a learning outcome test. Data analysis methods include prerequisite tests, namely normality and homogeneity tests. Subsequently, hypothesis testing is carried out using the t-test. The research instrument utilised comprises pre-test and post-test assessments. The findings indicate a significant difference between the average scores of the experimental and control classes. Data analysis shows that students’ learning outcomes in IPAS, using the Discovery Learning model, achieve an average score of 73.38 in the experimental class, while the control class obtains an average score of 64.59. Therefore, it can be concluded that the Discovery Learning model positively influences IPAS learning outcomes, and students taught through this model are more active and demonstrate better understanding compared to those taught using conventional methods.